Trends in out-of-school children and other basic education statistics - Jose Ramon G. Albert; Martin Joseph M. Raymundo (Philippine Institute for Development Studies (PIDS), 2016)
The Philippines has put a lot of importance to the basic education sector. The immediate past government provided more resources to the sector, in support of the Philippine Development Plan as well as to attain commitments to global goals, including the Millennium Development Goals and its successor, the Sustainable Development Goals (which include SDG4 to achieve quality education for all). In this paper, various education indicators sourced from administrative reporting systems of the Department of Education, as well as sample surveys conducted by the Philippine Statistics Authority, are examined for monitoring and evaluation of the basic education sector. Further, these data sources on education statistics are scrutinized for describing persisting disparities among various groups (e.g., boys versus girls, poor and nonpoor, urban and rural population), and for probing into why some children continue to be out of school. Measurement issues and policy implications are also discussed.
Keywords: 330; education indicators; out-of-school children (OOSC); monitoring and evaluation